History of teachers´ formation in WG 2 of ANPED annual meetings (2003-2012): research perspectives in the history of education - Joseane de Fátima Machado Silva (Universidade Estadual de Maringá, 2015)
Current essay identifies and analyzes how research involving the theme Teachers´ Formation has been shaped within the perspective of the History of Education in Work Group 2 (WG 2) of the annual meetings of the National Association of Postgraduate Studies and Research in Education (ANPED). Papers and posters published in the annual meetings over the last ten years (from 2003 to 2012) are analyzed. The methodology involved the identification and analysis of the research papers and posters published in the proceedings of the meetings. A survey of all papers and posters published in the proceedings of WG 2 was undertaken identifying, through a survey on the last decade, those which involved the theme Teachers´ Formation, coupled to the most investigated periods by the researchers who dealt with this specific theme.